The Impact of Authentic leadership on développement of créative work behaviorpsychological capital as a mediating variable : An Applied Study on the Yemeni Public Telecommunications Corporation - Awalki, Abdalah (Finance and Business Economies Review, 2019)
This study investigates the nature of the direct and indirect relationship between Authentic leadership and the development of creative work behavior in the Yemeni Public Telecommunications Corporation through psychological capital as a mediating variable. In order to achieve this objective, a sample of 285 employees was selected at the main headquarters of the Yemeni Public Telecommunications Corporation and its branches in Sana'a. A survey list was used to collect a primary data. The number of survey lists that was collected and be valid for analysis is 226 lists which represent 79% of the whole distributed survey lists. The results showed that there is a shortage in the level of practice of Authentic leadership by the managers of the Yemeni Public Telecommunications Corporation according to the attitudes of subordinates. Also, the level of psychological capital of the employees and their creative behavior is a moderate level. In addition, the results showed a significant relationship between the practice of Authentic leadership and the development of creative work behavior in the Yemeni Public Telecommunications Corporation. Finally, the results showed that psychological capital significantly mediates the relationship between Authentic leadership practice and the development of creative work behavior .